Unbelief, the Senses and the Body in Nicholas Bownde's The vnbeleefe of S. Thomas (1608) - McGhee, Patrick S. (Studies in church history, 2016)
Doubt and unbelief were central to the ways in which ministers and theologians in post-Reformation England thought and wrote about religion. Far from signalling spiritual failure, grappling with unbelief could be an important stage in developing the faith and religious understanding of the individual believer while establishing a role for physicality and the senses. Nicholas Bownde's The vnbeleefe of S. Thomas the Apostle, laid open for the comfort of all that desire to beleeue (1608) suggests that unbelief was relational and that belief required not only an acknowledgement of doubt but also extensive exploration of what doubtful and unbelieving experiences involved and how they were to be overcome. Bownde's work demonstrates that this ongoing spiritual conversation could make use of important scriptural examples such as the ‘Doubting Thomas’ episode in order to elucidate intimate theological problems for contemporary believers. This process suggests that early modern religion can only be properly understood with close reference to the role of doubt, unbelief and spiritual uncertainty in religious discourse because belief itself was predicated on the logical possibility of unbelief.